2015
DOI: 10.1007/s00394-014-0828-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional adequacy according to carbohydrates and fat quality

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 27 publications
1
38
0
5
Order By: Relevance
“…Other authors have shown a similar nutrient distribution in Spanish population [ 51 ]. Despite the fact that in our study total fat intake was higher than recommended for adult population, recent results from PREDIMED study have postulated that fat quality intake is a major nutritional determinant of quality of diet and cardiovascular benefits can be obtained with a relatively fat-rich diet [ 52 ]. Particularly, the adequate intake of MUFAs and PUFAs in our study, mainly due to a high consumption of olive oil, has been previously associated with a lower risk of CVD [ 53 ].…”
Section: Discussionmentioning
confidence: 61%
“…Other authors have shown a similar nutrient distribution in Spanish population [ 51 ]. Despite the fact that in our study total fat intake was higher than recommended for adult population, recent results from PREDIMED study have postulated that fat quality intake is a major nutritional determinant of quality of diet and cardiovascular benefits can be obtained with a relatively fat-rich diet [ 52 ]. Particularly, the adequate intake of MUFAs and PUFAs in our study, mainly due to a high consumption of olive oil, has been previously associated with a lower risk of CVD [ 53 ].…”
Section: Discussionmentioning
confidence: 61%
“…The Mediterranean diet (MedDiet) is characterized by the consumption of high amounts of vegetables, cereals (mostly unrefined), legumes, nuts and olive oil as the main source of fats, moderate intakes of fish and dairy products, low quantities of meat and meat products, and an optional moderate wine consumption (1)(2)(3) . Epidemiological studies have associated the MedDiet with a higher nutrient adequacy (4,5) and several investigations confirm its role in prevention of chronic diseases (6)(7)(8)(9)(10)(11)(12)(13) . Moreover, this pattern should not be considered like a set of foods only, but also as a cultural model.…”
mentioning
confidence: 99%
“…Moreover, self-reported questionnaires are subject to some degree of information bias. With the intention to avoid bias, participants reporting extreme total energy intakes were excluded from the analysis [ 17 ]. Furthermore, the relationship of all parameters may represent association and/or causality.…”
Section: Discussionmentioning
confidence: 99%
“…Participants reporting extreme total energy intakes (<500 or >3500 kcal/day in women or <800 or >4000 kcal/day in men) were excluded from the analysis [ 17 ]. For this reason, at baseline, 241 subjects were excluded (53 incomplete FFQ and 188 reporting extreme total energy intakes).…”
Section: Methodsmentioning
confidence: 99%